HBR guide to office politics - Dillon, Karen (Harvard Business Review Press, 2015)
Don't let destructive drama sideline your career. Every organization has its share of political drama: Personalities clash. Agendas compete. Turf wars erupt. But you need to work productively with your colleagues--even difficult ones--for the good of your organization and your career. How can you do that without compromising your personal values? By acknowledging that power dynamics and unwritten rules exist--and navigating them constructively. The "HBR Guide to Office Politics" will help you succeed at work without being a power grabber or a corporate climber. Instead you'll cultivate a political strategy that's authentic to you. You'll learn how to: Gain influence without losing your integrity; Contend with backstabbers and bullies; Work through tough conversations; Manage tensions when resources are scarce; Get your share of choice assignments; Accept that not all conflict is bad. Arm yourself with the advice you need to succeed on the job, from a source you trust. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.